A mechanism of ineffective erythropoiesis in β-thalassemia/Hb E disease - Lithanatudom,P. (Ferrata Storti Foundation, 2015)
Background Cells respond to stress stimuli through a number of response pathways, of which one of the most important and well characterized is the unfolded protein response. Despite a large body of work which suggests that stress in erythroblasts may play a pivotal role in the pathogenesis of β-thalassemia/Hb E disease, this pathway remains uninvestigated. Design and Methods Day 10 erythroblasts from normal controls and β-thalassemia/Hb E patients were subjected to internal (treatment with tunicamycin) and external (serum and growth factor withdrawal) stress stimuli and the activation of the unfolded protein response pathway was investigated. Results Normal erythroblasts responded to both internal and external stress by activating the unfolded protein response (UPR) pathway while in contrast, erythroblasts from β-thalassemia/Hb E patients only showed activation of the unfolded protein response pathway in response to internal stress. This was reflected by a markedly increased induction of apoptosis in serum and growth factor deprived β-thalassemia/Hb E erythroblasts as compared to control cells. Modulation of the levels of intracellular Ca2+ in thalassemic erythroblasts restored UPR activation during serum deprivation and significantly reduced the level of serum deprivation induced apoptosis to control levels. Conclusions These results suggest the failure of thalassemic erythroblasts to cope with cellular stress caused by an impaired UPR function as a result of high Ca2+ levels may exacerbate thalassemic cell death during erythropoiesis. © 2010 Ferrata Storti Foundation.